Application of Lineament Density Extraction Based on Digital Elevation Model for Geological Structures Control Analysis in Suwawa Geothermal Area - Intan Noviantari Manyoe; Ronal Hutagalung (Journal of Geoscience, Engineering, Environment, and Technology, 2022)
The tectonic condition of Gorontalo, which is located in the north of Sulawesi Island has implications for the spread of geothermal potential. The area in Gorontalo with the largest geothermal potential is the Suwawa area, Bone Bolango Regency. Therefore, this study aims to develop a model of lineament extraction from a digital elevation model and analyze the geological structure control based on the lineament distribution. This research is useful for the development of knowledge in the geothermal field, especially the study of permeability and structural control in geothermal areas. This research is beneficial for the community because it can detect the permeability zone in more detail which is the basis for the utilization of geothermal potential. The factors studied in this study are the geological lineament density and the geological structures. To achieve the research objectives, extraction methods and model analysis include analysis of permeable and control of geological structures. The lineament extraction model from the digital elevation model in the Suwawa geothermal area shows that there is a moderate to high agreement for lineament extraction from NATIONAL DEM data and low to moderate agreement for lineament extraction from SRTM data. The lineament distribution showing moderate to high density occupies the southern, eastern, and western parts of the Suwawa geothermal area. The presence of a lineament controls the circulation of geothermal fluids in the Suwawa geothermal area.